India: The mother of democracy is the land of justice - Sahoo, Jitendra (The Indian Journal of Political Science)
India i.e. Bharat is the mother of democracy and land of justice. With the inception of consultation, it was declared that we the people of India having solemnly resolved to constitutive the country as SSDR sate and to provide all it citizens Justice. Reproduced